Amusing Ourselves to Life: Fitness Consumerism and the Birth of Bio-Games. (December 2014) - Millington, Brad
Against the common perception that media consumption engenders inactivity, in recent years the technology sector has developed an extensive catalogue of games for bodily and cognitive exercise. Despite their popularity, however, and despite their potential ability to affect perceptions and experiences of health and fitness, there remains a shortage of academic research on video games of this kind. Drawing from earlier studies, the central contribution of this article lies in the introduction of "bio-play" and "bio-games" as terms for conceptualizing these new fitness products. The former term refers to the conjoining of self-care—specifically, self-assessments, surveillance, and discipline—and entertainment in games such as Nintendo's Wii Fit; the latter refers to the technological genre as a whole that is characterized by such activity. The prefix "bio" in each case reflects the contribution of new fitness technologies to the broader conjuncture in which they are located—namely, their discursive and material support of the (neoliberal) presumption that biological "self-improvement" is achievable through the marketplace. Acknowledging their possible benefits, in this analysis I also highlight concerns associated with the arrival of bio-games. These include the relations underlying the production of these technologies, their manner of proffering fitness services, and their representations of the "ideal" body and brain. I close by outlining challenges for researchers, educators, and policymakers that follow from industry's newfound promise that, with the help of new media, we can amuse ourselves to life.